Hydroquinone derivatives from the marine-derived fungus Gliomastix sp. Issue 49 (13th June 2017) - Elnaggar, Mohamed S.; Ebrahim, Weaam; Mándi, Attila; Kurtán, Tibor; Müller, Werner E. G.; Kalscheuer, Rainer; Singab, Abdelnasser; Lin, Wenhan; Liu, Zhen; Proksch, Peter
Abstract : A novel cytotoxic quinone/hydroquinone dimer from the marine-derived fungus Gliomastix sp. Abstract : Eight new hydroquinone derivatives, gliomastins A–D (1–4 ), 9- O -methylgliomastin C (5 ), acremonin A 1- O -β-d -glucopyranoside (6 ), gliomastin E 1- O -β-d -glucopyranoside (7 ), and 6′- O -acetyl-isohomoarbutin (8 ), together with seven known analogues were isolated from the marine-derived fungus Gliomastix sp. Their structures were elucidated by extensive spectroscopic analysis including 1D and 2D NMR measurements aided by DFT NMR calculations as well as MS data. TDDFT-ECD and OR calculations were performed to determine the absolute configurations of1 and the aglycones of6 and7 . Compound1 features a novel skeleton, biogenetically derived from a Diels–Alder reaction between derivatives of11 and13 . Compound2 represents a rare sulfur-containing alkaloid derived from the known hydroquinone13 . Compounds1, 10 and12 showed strong cytotoxicity against the L5178Y mouse lymphoma cell line with IC50 values of 1.8, 1.0 and 1.1 μM, respectively. Compound3 exhibited moderate antitubercular activity against Mycobacterium tuberculosis with a MIC value of 12.5 μM.